Freedom riders [videorecording (DVD)] - Nelson, Stanley, 1951-; Nelson, Stanley, 1951-; Nelson, Stanley, 1951-; Arsenault, Raymond (PBS Distribution, 2011)
This inspirational documentary is about a band of courageous civil-rights activists calling themselves the Freedom Riders. Gaining impressive access to influential figures on both sides of the issue, it chronicles a chapter of American history that stands as an astonishing testament to the accomplishment of youth and what can result from the incredible combination of personal conviction and the courage to organize against all odds.